‘Arab Spring’: The Influence of the Muslim Brotherhood and Their Vision of Islamic Finance and State (abstract) - Zidane Meriboute (Revue Internationale de Politique de Développement)
This chapter analyses the Muslim Brotherhood movement (Ikhwan al-muslimin) in its various guises. Born in the interwar period, this global, proselytising Islamic movement underwent a veritable resurgence, even a resurrection, in Muslim countries from the 1980s onwards. Founded in 1928 by the Egyptian Hassan al-Banna (1906–1949), the recent ‘Arab Spring’ phenomenon has given it fresh momentum. Significantly, the Muslim Brotherhood movement has taken the reins of Egypt, the most populous state in the Arab world. Wherever this movement gains a foothold, it creates its own labour unions, associations of students, doctors and workers, Islamic banking institutions, and so forth. More specifically, the chapter examines the nature of the Islamic state and the key characteristics of the politico-religious doctrine of the Muslim Brotherhood and its various offshoot Islamist parties, both in the Maghreb and elsewhere. The author sheds light on the Muslim Brotherhood’s economic, social and financial vision through an examination of the various techniques they employ with respect to Islamic finance. While the Muslim financial model is driven by considerations of social justice (‘adala ijtima’iya) and the rejection of usury (riba), it is nevertheless argued that its emphasis on profit maximisation renders this model’s vision essentially capitalist. The chapter thus calls for a refocusing and adaptation of the approach of Islamic banks in order to make their financing accessible for small projects undertaken by the disenfranchised.